Acute myeloid leukemia with 11q23 rearrangements: A study of therapy-related disease and therapeutic outcomes. (November 2020) - Menghrajani, K.; Zhang, Y.; Famulare, C.; Devlin, S.M.; Tallman, M.S.
Highlights: MLL rearrangements can occur in either the de novo or therapy-related setting. Most patients with therapy-related MLL- r AML had a t(9;11) or t(11;19). De novo MLL -r AML patients had a greater diversity of translocation partners. No difference in OS was seen between tAML and de novo MLL AML. Response to initial induction therapy was associated with improved survival. Abstract: We described the clinical features and outcomes for 63 adult patients with acute myeloid leukemia (AML) with a translocation involving the 11q23 locus ( MLL ) who were treated at Memorial Sloan Kettering Cancer Center (MSK). The population included 40 female (63 %) and 23 male (37 %) patients, with a median age of 51 years old (range 18–82 years). Of the 31 patients who had had an antecedent malignancy, 14 (45 %) had had breast cancer or DCIS and 22 (71 %) had received anthracycline-based systemic chemotherapy. The translocation partner for the 11q23 rearrangement was identified in 60 of the 63 patients (95 %) studied. The distribution of translocation partners differed for those who had previously received cytotoxic chemotherapy. Most patients with therapy-related disease had a 9p22 or 19p13 partner, as compared to those with de novo disease (95 % vs. 68 %, p = 0.023). Of the 30 patients who received all therapy under observation, 15 (50 %) patients had de novo disease and 15 (50 %) had received antecedent chemotherapy. No significant difference in survival was observed between groups (p = 0.44). Twenty-two patients received induction as up-front therapy, of whom 11 (50 %) achieved CR / CRi. The achievement of CR / CRi with one course of induction was associated with improved OS, with a 6-month OS of 73 % as compared to 23 % for those who did not (p = 0.018). The achievement of CR / CRi with a single course of induction may be a marker of favorable survival in this subtype of high-risk AML. Key Point: Response to a single induction was associated with favorable survival in this population.